2015
DOI: 10.1007/s10763-015-9690-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Lesson Study to Develop Elementary Preservice Teachers’ Pedagogical Content Knowledge for Teaching Nature of Science

Abstract: This study explored a modified version of Japanese Lesson Study to determine whether and how it influenced preservice elementary teachers in their abilities to deliver science lessons that included nature of science (NOS) to their own students. We used a case study approach that focused on one subset of a cohort of preservice elementary teachers within their field placement settings. Data sources included lesson plans, lesson feedback forms, videotapes of delivered lessons, and videotapes of lesson study feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 29 publications
(40 reference statements)
5
48
0
2
Order By: Relevance
“…In this activity, teachers can give constructive suggestion to the content, pedagogy, and technology. This finding is in line with Akerson et al (2017) that lesson study resulted in improving teachers' skill in planning the lesson, creating a positive learning environment, empower the student to learn and assess the student appropriately.…”
Section: Role Of Lesson Study In Teachers' Tpack Developmentsupporting
confidence: 83%
“…In this activity, teachers can give constructive suggestion to the content, pedagogy, and technology. This finding is in line with Akerson et al (2017) that lesson study resulted in improving teachers' skill in planning the lesson, creating a positive learning environment, empower the student to learn and assess the student appropriately.…”
Section: Role Of Lesson Study In Teachers' Tpack Developmentsupporting
confidence: 83%
“…Juhler (2017) concluded that pre-service teachers developed a more student-centered teaching approach after involved in a Lesson Study in physics since their lesson plan start considering more the students' difficulties, misconceptions, preferences and evaluation rather than simply focusing on student behavior. In addition, Akerson et al (2017) explored the development of PCK in teaching the nature of science in a Lesson Study conducted with pre-service primary teachers and concluded that the participants gave good suggestions about how to teach the topic in the classroom. However, they revealed difficulties in implementing the suggestions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Pongsanon, Akerson, & Rogers, 2011;Weiland et al, 2010) and CoRe (i.e. Nilsson & Loughran, 2011;Padilla, Ponce de León, Rembado, & Garritz, 2008;Rollnick, Bennett, Rhemtula, Dharsey, & Ndlovu, 2008).…”
Section: Deliberate Ref Lections Through Lesson Study and Content Repmentioning
confidence: 99%